Enhancement effect of bimetallic amide K2Mn(NH2)4 and in-situ formed KH and Mn4N on the dehydrogenation/hydrogenation properties of Li–Mg–N–H system - Gizer, Gökhan (2019)
In this work, we investigated the influence of the K2Mn(NH2)4 additive on the hydrogen sorption properties of the Mg(NH2)2 + 2LiH (Li–Mg–N–H) system. The addition of 5 mol% of K2Mn(NH2)4 to the Li–Mg–N–H system leads to a decrease of the dehydrogenation peak temperature from 200 ◦C to 172 ◦C compared to the pristine sample. This sample exhibits a constant hydrogen storage capacity of 4.2 wt.% over 25 dehydrogenation/rehydrogenation cycles. Besides that, the in-situ synchrotron powder X-ray diffraction analysis performed on the as prepared Mg(NH2)2 + 2LiH containing K2Mn(NH2)4 indicates the presence of Mn4N. However, no crystalline K-containing phases were detected. Upon dehydrogenation, the formation of KH is observed. The presence of KH and Mn4N positively influences the hydrogen sorption properties of this system, especially at the later stage of rehydrogenation. Under the applied conditions, hydrogenation of the last 1 wt.% takes place in only 2 min. This feature is preserved in the following three cycles.